1995
DOI: 10.1001/jama.1995.03530060037030
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Zinc Supplementation on Pregnancy Outcome

Abstract: Daily zinc supplementation in women with relatively low plasma zinc concentrations in early pregnancy is associated with greater infant birth weights and head circumferences, with the effect occurring predominantly in women with a body mass index less than 26 kg/m2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(37 citation statements)
references
References 38 publications
2
34
0
1
Order By: Relevance
“…After deficiency has been present for some time other manifestations may be recognized. They include retarded genital development and hypogonadism [46,[83][84][85][86], poor pregnancy outcomes and teratology [87][88][89][90][91][92][93], high morbidity and death from diarrhea, pneumonia, and other infections [94], and impaired brain function [71,[95][96]. No sign is pathognomonic.…”
Section: Physical Signs Of Zinc Deficiencymentioning
confidence: 99%
“…After deficiency has been present for some time other manifestations may be recognized. They include retarded genital development and hypogonadism [46,[83][84][85][86], poor pregnancy outcomes and teratology [87][88][89][90][91][92][93], high morbidity and death from diarrhea, pneumonia, and other infections [94], and impaired brain function [71,[95][96]. No sign is pathognomonic.…”
Section: Physical Signs Of Zinc Deficiencymentioning
confidence: 99%
“…33,91 The ability of supplemental calcium to decrease the risk of preterm delivery may be confined to high-risk 102,103 A clinical trial that randomly supplemented only women with plasma zinc levels below the median reported an increase in length of gestation of approximately 0.5 week (P = 0.06) and an increase in birthweight (about half of which was explained by the longer duration of gestation). 104 Studies of prenatal zinc supplementation have reported an improvement in fetal neurobehavioral development. 105 Zinc supplementation may also help protect against apoptosis of endothelial cells induced by TNF-a.…”
Section: Supplementation With Calcium and Magnesium With Zincmentioning
confidence: 99%
“…The zinc status is known to be important in various pregnancy outcome measures, such as small-for-dates infants [72]. An adequate zinc intake has been shown to be needed for successful implantation and nidation in animal models [73,74].…”
Section: Zincmentioning
confidence: 99%